دفاع وطن کے حوالے سے اسلامی تعلیمات: معاصر مسائل اور ان کا تدارک: "ISLAMIC TEACHINGS ON NATIONAL DEFENSE: CONTEPORARY CHALLENGES AND THEIR REMEDIES" (Al-Aasar, 2025)
The defense of one’s homeland holds a central place in Islamic teachings, as it is directly linked with the preservation of faith, life, and collective security. Islam not only permits but encourages the protection of the homeland against aggression, emphasizing preparation, unity, and justice as core principles of defense. In the contemporary era, the concept of national defense extends beyond physical warfare to include ideological, economic, and technological challenges. Muslim societies, including Pakistan, face complex threats such as cyber warfare, ideological invasion, political instability, terrorism, and economic dependency, all of which weaken national resilience. This study aims to explore the Islamic foundations of national defense in light of the Qur’an and Sunnah, analyze the modern challenges confronting the security of Muslim states, and propose strategic and ethical remedies grounded in Islamic principles. The research concludes that true defense in Islam is not limited to military readiness but also requires spiritual strength, intellectual awareness, economic stability, and social unity. Hence, adopting a holistic and faith-based defense framework is essential to safeguard both the sovereignty and ideological integrity of the Muslim Ummah.